2021
DOI: 10.48048/wjst.2021.22787
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carboxymethyl Glucomannan Concentration on the Properties of Glucomannan-Chitosan Hydrogel for Lactobacillus acidophilus FNCC 0051 Encapsulation

Abstract: The effect of porang (Amorphophallus oncophyllus) glucomannan concentration on the properties of glucomannan-chitosan hydrogel was investigated for Lactobacillus acidophilus FNCC 0051 encapsulation. The spherical shape with a continuous surface of the particle was self-assembly formed. The increase of glucomannan concentration from 0.3 to 0.9 % smoothly increased their small particle size from 1.08 ± 0.02 µm to 2.12 ± 0.00 µm and no significant change on the positive zeta potential values. The polydispersity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 37 publications
3
8
1
Order By: Relevance
“…The differences in the achieved encapsulation efficiencies might reflect the different encapsulant types and encapsulation methods used [ 12 ]. We previously showed that the same ratio of glucomannan and chitosan affected the encapsulation efficiency due to the chemical bonding of both polymers as well as due to the difference in electrostatic values between the core and the polymer influencing the degree of cell entrapment [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The differences in the achieved encapsulation efficiencies might reflect the different encapsulant types and encapsulation methods used [ 12 ]. We previously showed that the same ratio of glucomannan and chitosan affected the encapsulation efficiency due to the chemical bonding of both polymers as well as due to the difference in electrostatic values between the core and the polymer influencing the degree of cell entrapment [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…The particle size was also correlated with the encapsulation efficiency ( Table 1 ), as more cores could be trapped within larger hydrogel particles. The other factors found to influence the particle sizes were the concentration and viscosity of the solution [ 8 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations